A Study on Laboratory Evaluation of Warm Mix Asphalt Incorporated With Reclaimed Asphalt Pavement (International Journal of Innovative Research in Engineering & Management, 2021)
Sustainable Development Goal-11 envisions making cities and  human settlements inclusive, safe, resilient and sustainable. This  includes sustainable transport in the context of infrastructure,  public transport systems, good delivery networks, affordability,  efficiency and convenience of transportation, improving urban air  quality and health and reducing greenhouse gas emissions. Warm  mix asphalt (WMA) and reclaimed asphalt pavement (RAP) are  the most leading sustainable materials in asphalt concrete  pavements. WMA has been in use for quite some time; however,  innovations and increased usage have been stimulated by the  greater emphasis on sustainable infrastructure systems. WMA  enables decreased production temperatures with the help of wax,  water, or other chemicals. The effects of decreased production  temperatures include lowered fuel use and emissions, improved  compaction, and possible RAP concentration rises. RAP is the  recycled product of the old asphalt concrete pavements, and its  use leads to trimming in new aggregate and asphalt requirements.  However, substantial performance issues can rise from the  incorporation of WMA or RAP materials in asphalt concrete. This  study assesses the prospects of WMA technologies and their  integration with RAP. Initially, a detailed literature review was  done to understand the advantages, disadvantages, and past field and lab performance of WMA and RAP mixtures. Marshall Tests,  Indirect tensile strength test, aggregate coating and skid resistance  tests were conducted on virgin, and varied RAP proportioned  mixtures to examine the effects of RAP percentage on Optimum  bitumen content, Marshall stability and flow values, aggregate  coating and skid resistance. The results of this experiment  provided several crucial observations. First, the OBC decreased  with an increase in RAP percentage. Secondly, moisture  susceptibility, as well as aggregate coating, decreases with the  increase in RAP dosage. Furthermore, the inclusion of RAP to  WMA mixtures decreased the skid resistance of asphalt concrete  as determined by a portable skid resistance tester.
Keywords: Sustainability; RAP; Asphalt; Pavement; Recycle